Method for eluting aluminum and / or zinc ions
The problems of contamination and cost increase in complex agents in the prior art are solved by using alkaline eluents such as alkali metal hydroxides and ammonia hydroxides.
Patent Information
- Application Number
- JP2024556517
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-22
- Filing Date
- 2023-03-16
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2043-03-16
AI Technical Summary
Prior art In efficient and selective removal of aluminum and zinc ions from polymers with aminomethylphosphate content, complex agents are required, resulting in contamination and increased costs.
Alkaline eluents, including alkali metal hydroxides and ammonia hydroxides, or mixtures thereof, are used to efficiently and selectively remove aluminum and zinc ions.
Highly selective removal of aluminum and zinc ions is achieved, avoiding contamination of complex agents and increased costs.
Smart Images

Figure 2025510170000001 
Figure 2025510170000002 
Figure 2025510170000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a process for eluting aluminum and / or zinc ions from polymers containing aminomethylphosphonic acid groups. [Background technology]
[0002] Recycling of lithium-ion batteries is an essential technology to enable the transition towards more sustainable electromobility. Ion exchange resins represent a promising technology for removing impurities such as, for example, copper, aluminum and zinc from the electrolyte concentrates resulting from recycled lithium-ion batteries. The use of polymers containing phosphonate groups is known, for example, from WO 02 / 04311 and is particularly suitable for removing divalent and trivalent metal ions. From WO 02 / 04311 it is also known that it is possible to regenerate phosphonate group-containing polymers by using alkaline solutions containing tartrate, citrate, oxalate or EDTA ions, thereby removing the metal ions from them.
[0003] Virolainen et al. (Non-Patent Document 1) describe that aminomethylphosphonic acid group-containing polymers, such as Lewatit® MDS TP 260, are particularly suitable for removing aluminum and iron from concentrates of mixtures of aluminum, copper, manganese, iron, lithium, nickel and cobalt. For this purpose, Virolainen et al. developed a two-stage process in which metal ions are first bound to the aminomethylphosphonic acid group-containing polymer, then in a first step, copper, manganese and cobalt are eluted with sulfuric acid, the cobalt solution is re-adsorbed, and in a second step, aluminum is complexed and eluted with an alkaline potassium oxalate solution.
[0004] The elution process known from the prior art for eluting aluminum ion and / or zinc ion on the polymer containing aminomethylphosphonic acid groups is based on the use of complexing agent, because the binding affinity of aluminum ion and zinc ion to phosphonic acid group is very high.However, complexing agent is a compound that pollutes wastewater, i.e. has ecological disadvantages, so it must be removed again.This increases the cost of the process. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2012 / 113657 Brochure [Non-patent literature]
[0006] [Non-Patent Document 1] S.Virolainen,T.Vesselborg,A.Kaukinen,T.Sainio,Hydrometallurgy,2021,202,105602,p.1 to 9 Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, there remains a need for a process capable of eluting aluminum ions and / or zinc ions with high selectivity from aminomethylphosphonic acid group-containing polymers. [Means for solving the problem]
[0008] Surprisingly, it has now been found that aluminium ions and / or zinc ions can be eluted with high selectivity from the polymer containing aminomethylphosphonic acid groups if the base used for elution is a base selected from the group of alkali metal hydroxides and ammonium hydroxide, or a mixture of said bases.
[0009] The present invention therefore provides a process for eluting aluminum and / or zinc ions, in which an aminomethylphosphonic acid group-containing polymer, or a salt thereof, at least partially carrying aluminum and / or zinc ions, is mixed with a base selected from the group of alkali metal hydroxides and ammonium hydroxide, or a mixture of said bases, to elute the aluminum and / or zinc ions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The scope of the present invention includes all the definitions of radicals, parameters and descriptions detailed above and hereinafter, referred to as general terms or within preferred ranges, including the various combinations between each other, i.e., between the respective ranges and the preferred ranges.
[0011] It is preferred if the aminomethylphosphonic acid group-containing polymer is an aminomethylphosphonic acid group-containing polystyrene copolymer. It is even more preferred if the aminomethylphosphonic acid group-containing polymer is an aminomethylphosphonic acid group-containing polystyrene-divinylbenzene copolymer.
[0012] Examples of the aminomethylphosphonic acid group-containing polymer include aminomethylmonophosphonic acid group-containing polymer, aminomethyldiphosphonic acid group-containing polymer, and their salts. The aminomethylphosphonic acid group-containing polymer salt is preferably an alkali metal salt, an alkaline earth metal salt, or a metal salt of Group III to XII of the Periodic Table of Elements. The aminomethylphosphonic acid group-containing polymer salt is preferably a sodium, potassium, lithium, magnesium, calcium, iron, copper, manganese, cobalt, or nickel salt. It is particularly preferred that the aminomethylphosphonic acid group-containing polymer salt is a sodium, potassium, lithium, cobalt, or nickel salt. It is particularly preferred to use sodium, potassium, or nickel salt as the aminomethylphosphonic acid group-containing polymer salt.
[0013] The polystyrene copolymers used are preferably copolymers of monovinylaromatic monomers selected from the group of styrene, vinyltoluene, ethylstyrene, α-methylstyrene, chlorostyrene or chloromethylstyrene and mixtures of these monomers, and polyvinylaromatic compounds (crosslinkers) selected from the group of divinylbenzene, divinyltoluene, trivinylbenzene, divinylnaphthalene and / or trivinylnaphthalene.
[0014] It is particularly preferred if the polystyrene copolymer backbone used is a styrene / divinylbenzene copolymer, which is a crosslinked copolymer using divinylbenzene. It is preferred to use technical grades of divinylbenzene, which may contain up to 30% by weight of ethylvinylbenzene. The styrene / divinylbenzene copolymer thus also includes copolymers which further contain ethylvinylbenzene as a monomer.
[0015] It is preferred that the polymer has a spherical morphology.
[0016] The aminomethylphosphonic acid group-containing polymer preferably has a macroporous structure.
[0017] The terms "microporous" or "gel-like" / "macroporous" have already been described in detail in the technical literature, for example in Seidl, Malinsky, Dusek, Heitz, Adv. Polymer Sci., 1967, Vol. 5, pp. 113 to 213. Possible methods for measuring the porosity, such as mercury porosimetry and BET measurement, are likewise described in said literature. The pores of the macroporous polymers of the aminomethylphosphonic acid group-containing polymers generally and preferably have a diameter of 20 nm to 100 nm.
[0018] It is preferred that the aminomethylphosphonic acid group-containing polymer has a monodisperse distribution.
[0019] In this application, a monodisperse material is one in which at least 90% by volume or 90% by weight of its particles have a diameter that falls within a ±10% interval from the most common diameter.
[0020] For example, for a material having a maximum diameter of 0.5 mm, at least 90% by volume or 90% by mass is within the size interval of 0.45 mm to 0.55 mm; for a material having a maximum diameter of 0.7 mm, at least 90% by volume or 90% by mass is within the size interval of 0.77 mm to 0.63 mm.
[0021] The aminomethylphosphonic acid group-containing polymer has a diameter (d 50 ) is preferably present.
[0022] It has a diameter of 250μm to 450μm (d 50 It is quite particularly preferred if the
[0023] Aminomethylphosphonic acid group-containing polymers can be prepared according to known processes, for example by phthalamidomethylation of styrene-divinylbenzene copolymers and functionalization of the amino groups thus obtained by reaction with PH acidic compounds in a sulfuric acid-containing suspension using formalin. They are also commercially available, for example as Lewatit® MDS TP 260 (from LANXESS Deutschland GmbH).
[0024] The average degree of substitution represents the statistical ratio between unsubstituted aminomethyl groups, aminomethyl groups monosubstituted with phosphonic acid groups, and aminomethyl groups disubstituted with phosphonic acid groups in the aminomethylphosphonic acid group-containing polymer. The average degree of substitution can therefore be from 0 to 2. At a degree of substitution of 0, no substitution occurs and the aminomethyl groups are present as primary amine groups. At a degree of substitution of 2, all aminomethyl groups in the resin are present disubstituted with phosphonic acid groups. At a degree of substitution of 1, from a statistical point of view, all aminomethyl groups in the resin are present in monosubstituted form.
[0025] In the aminomethylphosphonic acid group-containing polymer, the average degree of substitution of aminomethyl groups with phosphonic acid groups is preferably 1.4 to 2.0.
[0026] It is preferred that the aminomethylphosphonic acid group-containing polymer has a total hydrogen capacity of 2.5 mol to 7.0 mol per liter of resin, and it is very particularly preferred if the aminomethylphosphonic acid group-containing polymer has a total hydrogen capacity of 3.0 to 3.4 mol per liter of resin.
[0027] The total capacity of the aminomethylphosphonic acid group-containing polymers is determined in accordance with DIN 54403 (Testing of ion exchangers - Determination of the total capacity of cation exchangers).
[0028] For use as the aminomethylphosphonic acid group-containing polymer, a chelating resin having the functional group of component (I) is preferred. [ka] [In the formula, [ka] is a polystyrene copolymer backbone, R 1 and R2 may be the same or different and independently represent -CH2PO(OX 1 )2 and -CH2PO(OH)OX 2 or hydrogen, where R 1 and R 2 and cannot both be hydrogen at the same time, 1 and X 2 are independently hydrogen, sodium, potassium, or lithium.
[0029] R 1 and R 2 are independently -CH2PO(OX 1 )2 and -CH2PO(OH)OX 2 It is preferable that X 1 and X 2 is preferably H.
[0030] In its polystyrene copolymer backbone, -CH2-NR 1 R 2 A group is attached to the phenyl group.
[0031] The aminomethylphosphonic acid group-containing polymer is preferably a macroporous, monodisperse chelating resin having the functional group of component (I).
[0032] The aminomethylphosphonic acid group-containing polymer may partially or entirely carry aluminum ions and / or zinc ions.
[0033] The aminomethylphosphonic acid group-containing polymer preferably supports aluminum ions and / or zinc ions in a range of 10 mol % to 90 mol % based on the total capacity of the polymer.
[0034] The alkali metal hydroxides used are preferably sodium hydroxide and potassium hydroxide, and are preferably present in an aqueous solution.
[0035] It is preferred that the alkali metal hydroxide solution contains between 5% and 20% by weight of alkali metal hydroxide, and it is particularly preferred if the alkali metal hydroxide solution contains between 6% and 12% by weight of alkali metal hydroxide.
[0036] In a more preferred embodiment, the alkali metal hydroxide solution contains 5% to 20% by weight of alkali metal hydroxide, and 79% to 94% by weight of water, and up to 1% by weight of organic solvent or other impurities such as alkaline earth metal hydroxide or potassium oxalate, the proportion of potassium oxalate, if present, being less than 0.1% by weight in all cases.
[0037] In a more preferred embodiment, the alkali metal hydroxide solution contains 6% to 12% by weight of alkali metal hydroxide and 87% to 93% by weight of water, but up to 1% by weight of organic solvent or other impurities such as alkaline earth metal hydroxide or potassium oxalate may be present. If potassium oxalate is present, its proportion is in all cases less than 0.1% by weight.
[0038] In a more preferred embodiment, the alkali metal hydroxide solution comprises 5% to 20% by weight of alkali metal hydroxide and 80% to 95% by weight of water, the total amount of these compounds being 100% by weight.
[0039] For use as ammonium hydroxide, it is preferred to use an aqueous solution of ammonia at a concentration between 15% and 35% by weight.
[0040] In a more preferred embodiment, the ammonium hydroxide solution contains 15% to 35% by weight of alkali metal hydroxide and 84% to 64% by weight of water, but up to 1% by weight of organic solvent or other impurities such as alkaline earth metal hydroxide or potassium oxalate may be present. If potassium oxalate is present, its proportion is in all cases less than 0.1% by weight.
[0041] In a further preferred embodiment, the base used does not contain any complexing agent. In the context of the present invention, a complexing agent is preferably a solution containing tartrate, citrate, oxalate or EDTA ions. It is even more preferred that the base does not contain oxalate ions, in particular potassium oxalate.
[0042] The elution can be carried out by a batch process or by application to a column. The amount of base that must be applied for elution is preferably between 1 and 10 column volumes of polymer, particularly preferably between 3 and 7 column volumes of polymer.
[0043] In the elution, the pH of the elution solution is preferably 10-14.
[0044] The elution is preferably carried out at a temperature between 60° C. and 90° C. To achieve this temperature, the base may be heated or alternatively the aminomethylphosphonic acid group-containing polymer may be heated in the column process, for example and preferably by means of a heating coil.
[0045] After elution, the aminomethylphosphonic acid group-containing polymer can be regenerated by contacting with an acid. In this step, on the one hand, impurities are removed, but on the other hand, the aminomethylphosphonic acid group-containing polymer is converted back into the H-form. This allows the resin to carry metal ions again. It is preferable to use an inorganic acid as the acid for regenerating the aminomethylphosphonic acid group-containing polymer. The inorganic acids used are preferably sulfuric acid, hydrochloric acid, and nitric acid. It is particularly preferable to use sulfuric acid to regenerate the aminomethylphosphonic acid group-containing polymer.
[0046] To regenerate the aminomethylphosphonic acid group-containing polymer, it is preferable to use sulfuric acid at a concentration of 5% to 20% by weight.
[0047] In a further preferred embodiment, the present invention includes a process for eluting aluminum ions and / or zinc ions, wherein at least one chelating resin having the functional group of component (I) is [ka] [In the formula, [ka] is a polystyrene copolymer backbone, R 1 and R 2 may be the same or different and independently represent -CH2PO(OX 1 )2 and -CH2PO(OH)OX 2 or hydrogen, where R 1 and R 2 and cannot both be hydrogen at the same time, 1 and X 2 are independently hydrogen, sodium, potassium, and lithium. In step a), an aqueous solution of metal ions, comprising aluminum ions and / or zinc ions and optionally further metal ions, is brought into contact with a chelating resin, In step b) the aluminium and / or zinc ions are eluted using an aqueous solution of an alkali metal hydroxide or an aqueous solution of ammonium hydroxide or a mixture of these bases.
[0048] Step a) Metal ions and / or aluminum ions and / or zinc ions are brought into contact with a chelating resin having functional groups of component (I) in an aqueous solution of the metal ions. The adsorption of the metals can be carried out by a batch process or by application to a column. The adsorption is preferably carried out in a column process.
[0049] In step a), it is possible to use aluminum and / or zinc ions in a concentration between 10 μg / L and 5 g / L. It is preferable to use aluminum and / or zinc ions in a concentration between 1 mg / L and 1 g / L. Further metal ions may be supported in contact with a chelating resin having the functional group of component (I). Preferably, the metallic iron, copper, manganese, cobalt, nickel and lithium ions may be used as metal ions. It is preferable to use divalent or trivalent iron ions. It is preferable to use divalent copper, manganese, cobalt and / or nickel ions. It is preferable to use trivalent aluminum ions. It is preferable to use divalent zinc ions. It is particularly preferable to use lithium, nickel and cobalt ions. It is even more preferable to use nickel and cobalt ions.
[0050] In step a), an aqueous solution of metal ions of aluminium, nickel and cobalt ions is preferably applied to the chelating resin.
[0051] It is preferred that the molar ratio of aluminum ions to nickel ions and / or cobalt ions in the application in step a) is between 0.5 and 1.5.
[0052] It is preferred that the weight ratio of metal ions to aluminum ions and / or zinc ions in the chelating resin in step a) is from (100:1) to (2:1).
[0053] The weight ratio of lithium ions to aluminum ions and / or zinc ions in the chelating resin in step a) is preferably from (100:1) to (2:1).
[0054] It is preferred that the weight ratio of cobalt ions to aluminum ions and / or zinc ions in the chelating resin in step a) is from (100:1) to (2:1).
[0055] It is preferred that the weight ratio of manganese ions to aluminum ions and / or zinc ions in the chelating resin in step a) is from (100:1) to (2:1).
[0056] The weight ratio of copper ions to aluminum ions and / or zinc ions in the chelating resin in step a) is preferably from (100:1) to (2:1).
[0057] The weight ratio of iron ions to aluminum ions and / or zinc ions in the chelating resin in step a) is preferably from (100:1) to (2:1).
[0058] It is preferred that the weight ratio of nickel ions to aluminum ions and / or zinc ions in the chelating resin in step a) is from (100:1) to (2:1).
[0059] In step a), it is preferred to use an inorganic metal salt solution as the aqueous solution of metal ions. The inorganic metal salts used are particularly preferably nitrates, hydrochlorides or sulfates. It is very particularly preferred to use metal sulfates. It is preferred to use cobalt(II) sulfate, nickel(II) sulfate and aluminium(III) sulfate.
[0060] In a further preferred embodiment, in step a), the chelating resin having the functional groups of component (I) is loaded with aluminum ions, which may contain further metal ions, but in the absence of zinc ions.
[0061] In step a), it is preferred to use a chelating resin having a functional group of component (I) with a specific flow rate of 2 to 10 column volumes / hour (BV / h).
[0062] In step a), it is preferred to use 0.5 to 1.5 equivalents of a chelating resin having a functional group of component (I) per equivalent (Eq) of aluminum ions and / or zinc ions.
[0063] In step a), the chelating resin containing the functional group of component (I) is preferably loaded with metal ions at a pH of 1.5 to 6.0. This pH is often already present in the aqueous solution used, since the metal ions used constitute Lewis acids. If this pH is not present, it is possible to adjust the pH using an acid, preferably an inorganic acid. For this purpose, it is preferable to use sulfuric acid, hydrochloric acid or nitric acid. It is particularly preferable to use sulfuric acid.
[0064] Step b) In step b) aluminum and / or zinc ions are eluted from the chelating resin carrying the functional groups of component (I). Trivalent aluminum ions are preferred for use in step a) and eluted in step b). Divalent zinc ions are preferred for use in step a) and eluted in step b). The elution is preferably carried out using a solution of an alkali metal hydroxide. In step b), aluminum ions are preferably eluted.
[0065] The process according to the invention, which selectively removes aluminum and / or zinc ions from aminomethylphosphonic acid group-containing polymers and / or chelating resins containing functional groups of component (I) using solutions of alkali metal hydroxides and / or ammonium hydroxide, opens the way to selectively treat metal-containing lithium waste from used batteries.
[0066] method ICP The ion concentration can be measured by methods known to the skilled person from the prior art. In the process according to the invention, it is preferred to measure the ion concentration by means of an inductively coupled plasma spectrometer (ICP).
[0067] In this case, the mobile phase from the ion exchange resin column was fractionated into 10 mL fractions and analyzed by means of ICP to determine the ion concentrations.
[0068] Measuring total capacity The total capacity of the functional chelating resin of component (I) is determined in accordance with DIN 54403 (Testing of ion exchangers - Determination of the total capacity of cation exchangers).
[0069] Measuring the diameter of polymers The diameter of the polymer is measured according to DIN 54407 (Testing of ion exchange resins - Determination of bead size distribution), where the diameter d50 is the diameter of the polymer or polymer particles at which 50% of the polymer passes through a sieve with a mesh size of 0.5 mm and 50% remains. EXAMPLES
[0070] Example 1 A. Loading of aluminum, nickel, and cobalt onto macroporous and monodisperse chelating resins having functional groups of component (I) 200 mL of a chelating resin having a functional group of component (I), in the H form, 1 and R 2 are independently -CH2PO(OX 1 )2 and -CH2PO(OH)OX 2 where X 1 and X 2 is H (Lewatit® MDS TP 260, degree of substitution of aminomethyl groups by phosphonic acid groups: 2.0, total capacity: 3.2 mol / L, H form, d 50 (0.385 mm, monodisperse and macroporous) is dispersed in deionized water in a beaker with stirring and adjusted to pH=4 using H2SO4. Then, 250 mL of Co 2+ / Ni 2+ / Al 3+ An aqueous solution of sulfates of 6.95 g (0.118 mol / 0.027 g / L) cobalt, 6.93 g (0.118 mol) nickel, and 3.20 g (0.118 mol) aluminum was gradually added. During the addition of the solution, the pH of the supernatant of the ion exchange resin dropped from 4.0 to 1.9. The supernatant solution was then completely decanted and volumetrically analyzed. The chelating resin was washed several times with deionized water and subjected to suction to remove the adhering Co, Ni, and Al (850 mL washing water). The loading capacity of the chelating resin with the functional group of component (I) was calculated from the drop in Al, Ni, and Co in the supernatant to be 10.9 g / L (0.4 mol / L) for Al, 0.8 g / L (0.0135 mol / L) for Ni, and 1.1 g / L (0.0135 mol / L) for Co. 37.8% of the total capacity of the resin was loaded with aluminum ions.
[0071] B. Selective dissolution of aluminum using NaOH and its regeneration using dilute sulfuric acid In the next step, 20 mL of the chelating resin having the functional group of component (I) from A is eluted with 100 mL of 9 wt% NaOH aqueous solution under stirring at 80° C. for 3 hours. The alkaline solution is then decanted off. Subsequently, a portion of the fully regenerated resin is dried and digested in a microwave oven. The concentrations of aluminum, nickel and cobalt are measured by means of ICP (inductively coupled plasma spectrometry). The concentration of aluminum is below the detection limit. The concentrations of nickel and cobalt on the chelating resin having the functional group of component (I) are unchanged within the detection limit. The chelating resin thus remaining is thoroughly washed and regenerated with 100 mL of 15 wt% H2SO4 at room temperature under stirring for 1 hour. After a washing step with 80 mL of deionized water, the NaOH on the surface is removed. By adding 15 wt. % H2SO4, essentially 100 wt. % of the nickel and cobalt remaining on the ion exchange resin was eluted, within the detection limit.
Claims
1. 1. A process for eluting aluminum ions and / or zinc ions, comprising: Mixing the aminomethylphosphonic acid group-containing polymer, or a salt thereof, at least partially carrying aluminum ions and / or zinc ions, with a base selected from the group of alkali metal hydroxides and ammonium hydroxide and mixtures of bases thereof, The aluminum ions and / or zinc ions are eluted. A process characterized in that
2. 2. The process according to claim 1, characterized in that as the aminomethylphosphonic acid group-containing polymer an aminomethylphosphonic acid group-containing polystyrene-divinylbenzene copolymer is used.
3. 3. The process according to claim 1 or 2, characterized in that the average degree of substitution of aminomethyl groups by phosphonic acid groups in the aminomethylphosphonic acid group-containing polymer is between 1.4 and 2.
0.
4. The process according to any one of claims 1 to 3, characterized in that the base does not contain any potassium oxalate.
5. The aminomethylphosphonic acid group-containing polymer has a diameter (d 50 5. The process according to claim 1, wherein the first and second halves of the reaction mixture are fused together.
6. 6. The process of claim 5, wherein at least 90% by volume or mass of the particles have a diameter within ±10% of the most common diameter.
7. 7. The process according to claim 1, wherein an aqueous alkali metal hydroxide solution is used at 6% to 12% by weight.
8. A process according to any one of claims 1 to 7, characterized in that it involves eluting aluminium ions.
9. The process according to any one of claims 1 to 8, characterized in that a chelating resin having functional groups of component (I) is used as the aminomethylphosphonic acid group-containing polymer: 【Chemistry 1】 [In the formula, 【Chemistry 2】 is a polystyrene copolymer backbone, R 1 and R 2 may be the same or different, and each independently represents -CH 2 PO (OX 1 ) 2 and -CH 2 PO(OH)OX 2 or hydrogen, where R 1 and R 2 and cannot both be hydrogen at the same time, 1 and X 2 are independently hydrogen, sodium, potassium, or lithium.
10. A process for eluting aluminum ions and / or zinc ions, comprising: at least one chelating resin having a functional group of component (I): 【Chemistry 3】 [In the formula, 【Chemistry 4】 is a polystyrene copolymer backbone, R 1 and R 2 , X 1 and X 2 is as defined in claim 9. having In step a) an aqueous solution of metal ions comprising aluminum ions and / or zinc ions and optionally further metal ions is brought into contact with said chelating resin, In step b) the aluminum and / or zinc ions are eluted using an aqueous solution of an alkali metal hydroxide or / and an aqueous solution of ammonium hydroxide. A process characterized in that
11. R 1 and R 2 may be the same or different, and each independently represents -CH 2 PO (OX 1 ) 2 and -CH 2 PO(OH)OX 2 11. The process according to claim 10, characterized in that
12. X 1 and X 2 The process of claim 11 , wherein
13. The process according to any one of claims 10 to 12, characterized in that an aqueous solution of metal ions of aluminium, nickel and cobalt ions is applied to the chelating resin in step a).
14. 14. The process according to claim 13, characterized in that in step a) the molar ratio of the aluminum ions to the nickel ions and / or the cobalt ions is between 0.5 and 1.
5.
15. 15. The process according to any one of claims 10 to 14, characterized in that the aqueous solution of metal ions comprising aluminum, nickel and cobalt ions applied to the chelating resin in step a) has a pH of 1.5 to 6.0.
Citation Information
Patent Citations
Method for separating and purifying amino acid
JP1993032599A
Improved cation removing method using chelate resin
JP2011116944A
Brine purification method
JP2017537779A
Method for the separation of metal ions that are divalent or higher from strong acids or highly acidic media
WO2012113657A1